2022
DOI: 10.1186/s13046-022-02425-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel early pancreatic cancer biomarkers KIF5B and SFRP2 from “first contact” interactions in the tumor microenvironment

Abstract: Background Pancreatic cancer is one of the most difficult cancers to detect early and most patients die from complications arising due to distant organ metastases. The lack of bona fide early biomarkers is one of the primary reasons for late diagnosis of pancreatic cancer. It is a multifactorial disease and warrants a novel approach to identify early biomarkers. Methods In order to characterize the proteome, Extracellular vesicles (EVs) isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…To characterize the protein composition of plasma EV preparations purified using Tymora’s non-antibody-based affinity EVtrap™ proprietary technology (designed to quantitatively capture membrane-bound vesicles including exosomes and validated in multiple peer-reviewed publications [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ), we assessed the enrichment in exosomal proteins curated by the ExoCarta Database. EVs were highly enriched in exosomal proteins, including 87 of the top 100 Exocarta proteins and nanoparticle tracking analysis (NTA) demonstrated size distributions consistent with preparations enriched in small EVs ( Figure 1 A-E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize the protein composition of plasma EV preparations purified using Tymora’s non-antibody-based affinity EVtrap™ proprietary technology (designed to quantitatively capture membrane-bound vesicles including exosomes and validated in multiple peer-reviewed publications [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ), we assessed the enrichment in exosomal proteins curated by the ExoCarta Database. EVs were highly enriched in exosomal proteins, including 87 of the top 100 Exocarta proteins and nanoparticle tracking analysis (NTA) demonstrated size distributions consistent with preparations enriched in small EVs ( Figure 1 A-E).…”
Section: Resultsmentioning
confidence: 99%
“…EV purification was conducted as described by Nunez Lopez and colleagues [19] , using EVtrap™ (Tymora Analytical, Lafayette, IN, USA), a non-antibody- bead-based affinity technology developed to specifically and quantitatively isolate EVs. The EVtrap™ technology has been further described and validated in detail elsewhere [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] . In short, frozen plasma samples were thawed and large debris removed by centrifugation at 2500×g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Further expression correlation analysis confirmed that ULK2 was involved in cell cycle and meiosis, indicating the importance of ULK2 in disease progression as exosomal ULK2 may exert pro-proliferation function when transported to target cells. However, pancreatic cancer derived exosomes cannot induce changes in distant organ metastases in in vivo models, but alter early murine gut microbiome ( 36 ). The detailed mechanism of ULK2 should be verified experimentally in future.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-omics profiling studies can provide new markers for PC diagnosis. Proteomic analysis of EVs derived from co-cultured epithelial and stromal cells in the condition mimicking TME showed that kinesin family member 5B and secreted frizzled related protein 2 had promising values as early PC biomarkers[ 84 ]. PancRISK score evaluated by three urine markers, including lymphatic vessel endothelial hyaluronan receptor 1, regenerating family member 1 beta, and trefoil factor 1, showed reasonable sensitivity and specificity for PDAC detection compared to CA 19-9[ 85 ].…”
Section: Diagnostic and Prognostic Markers For Pancreatic Cancermentioning
confidence: 99%